Highly Sensitive Electrochemical Determination of Dopamine with an Overoxidized Polypyrrole Nanofiber Pencil Graphite Electrode - Koyun, Ozge; Gursu, Hurmus; Gorduk, Semih; Sahin, Yucel (ESG, 2017)
We investigated the use of an overoxidized nanofiber polypyrrole (OONfPPy) modified pencil graphite electrode (PGE) as a sensor for the determination of dopamine (DA) in this work. The performance of the modified electrode was studied using differential pulse voltammetric method. The surface of the modified electrode was characterized by an electrochemical impedance spectroscopy (EIS) and scanning electron microscope (SEM). The calculated electroactive areas of the bare electrode and OO(10)NfPPy(5)PGE were found to be 4.54 x 10(-8) cm(2) and 1.05 x 10(-6) cm(2), respectively. The sensor (OO(10)NfPPy(5)PGE) showed a high selectivity to DA with a detection limit of 6.95 x 10(-9) M (S/N= 3). To demonstrate the validity of the sensor for the determination of DA, pharmaceutical and human serum samples were performed.
Keywords: Dopamine; Polypyrrole; Electropolymerization; Pencil Graphite Electrode; Sensor; GLASSY-CARBON ELECTRODE; ASCORBIC-ACID; URIC-ACID; GRAPHENE OXIDE; SELECTIVE DETERMINATION; PASTE ELECTRODE; GOLD ELECTRODE; SERUM SAMPLES; NANOTUBES; Electrochemistry